Unleashing Entrepreneurial Potential in Healthcare: Exploring the Mediating Role of Entrepreneurial Self-Efficacy in the Relationship between Positive Psychological Capital, Perceived Desirability, and Feasibility - Shahzadi, Irram; Ali, Umair; Arshad, Rabbia (Pakistan Journal of Humanities and Social Sciences, 2024)
Medical education is paying more emphasis to entrepreneurial intention, or the desire to start a business. This study aims to bring the entrepreneurial potential in healthcare, to the forefront. Therefore, this study intends to envisage the entrepreneurial intent by investigating the impact of positive psychological capital, perceived desirability and feasibility among health sciences undergraduates. The mediating role of self-efficacy (a part of perceived feasibility) is correspondingly examined. In this explanatory study, the data was gathered from a sample of 278 health science’ undergraduates through survey questionnaire. SPSS-28 and AMOS-28 were used to analyze the collected data. By employing the SEM technique, it is found that positive psychological capital, perceived desirability (personal attraction towards entrepreneurship, perceived social norms) and perceived feasibility (perceived behavioral control) have a substantial and encouraging influence on entrepreneurial intent. Likewise, self-efficacy (a part of perceived feasibility) acts as a mediation between the predictors and the outcome variable. It is concluded that health sciences undergraduates' positive psychological capital, perceived desirability and feasibility momentously encourage their entrepreneurial intention. The study results help attaining the socioeconomic intensification by readdressing the health sciences undergraduates’ EI. The results also instigate the healthcare sector’s policymakers to formulate policies for endorsing training to uplift self-development and EI among health sciences undergraduates.